2017
DOI: 10.1186/s13028-017-0318-8
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic genotype of major piroplasm surface protein associated with anemia in Theileria orientalis infection in cattle

Abstract: Serious disease outbreaks in cattle caused by Theileria orientalis have emerged in the Asia–Pacific region. Genetic variables of the major piroplasm surface protein (MPSP) expressed on the surface of the piroplasm inside T. orientalis-infected erythrocytes are considered to be associated with variation in the pathogenicity of T. orientalis. Our study describes the clinically relevant MPSP types associated with anemia in Theileria-infected cattle. These results revealed that MPSP expression plays an important r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Phylogenetic analysis using major piroplasm surface protein (MPSP) sequences of numerous isolates identified 11 allelic genotypes [ 2 ], with the Buffeli, Chitose, p32, and Ikeda genotypes being most prevalent in Japan, Australia, New Zealand, and the U.S [ 2 , 3 ]. T. orientalis genotypes vary widely in virulence [ 4 ]. The Ikeda genotype results in severe infection in 1–6% of infected animals [ 5 , 6 ], while infection with the Buffeli genotype is almost always clinically silent [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analysis using major piroplasm surface protein (MPSP) sequences of numerous isolates identified 11 allelic genotypes [ 2 ], with the Buffeli, Chitose, p32, and Ikeda genotypes being most prevalent in Japan, Australia, New Zealand, and the U.S [ 2 , 3 ]. T. orientalis genotypes vary widely in virulence [ 4 ]. The Ikeda genotype results in severe infection in 1–6% of infected animals [ 5 , 6 ], while infection with the Buffeli genotype is almost always clinically silent [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…When multiple B. bovis strains with distinct MSA-1 variants are transmitted by vector ticks, a new variant could probably be generated within ticks' mid-gut via genetic exchange, which might be the reason for the emergence and expansion of new variants in cattle populations [32]. The clinical significance of infection with distinct B. bovis variants has not been recorded; however, it was confirmed that several variants of T. orientalis and B. rossi were closely associated with outbreaks of theileriosis and babesiosis, respectively [35][36][37]. The relationship between genetic variants in the MSA genes and clinical status remains unknown, and requires investigation.…”
Section: Discussionmentioning
confidence: 98%
“…Regardless, the Ikeda genotype has been associated with recent clinical outbreaks in New Zealand [67,96,97]. Another Korean study [74] also suggested Chitose to independently establish clinical infection in cattle, but mixed infections were not accounted for in the study.…”
Section: Clinical Disease Infection Dynamics and The Immune Responsementioning
confidence: 96%
“…However, some studies have suggested MPSP genotypes Chitose (Type 1) [46, 74] and 7 [38] to be associated with clinical disease. The clinical relevance of these genotypes cannot be confirmed as COX III and 18S rRNA genes were used to characterise the samples instead of the MPSP gene in one study [46] or the possibility of mixed infections with Ikeda genotype was not investigated [1,38,74]. Nonetheless, Type 7 is phylogenetically related to the Ikeda genotype [1], and may indeed represent a pathogenic genotype…”
Section: Global Distribution Of T Orientalismentioning
confidence: 99%